Analysis of Silhouette Coefficient Evaluation with Euclidean Distance in the Clustering Method (Case Study: Number of Public Schools in Indonesia) - Dedy Hartama; Mawaddah Anjelita (Institute of Computer Science (IOCS), 2022)
This study aims to find out how much the silhouette coefficient value is obtained from calculating the distance from the data to the centroid using the euclidean distance in the k-means method and to provide input in science for further research in developing the k-means method. To solve this problem, researchers use the k-means method with silhouette coefficient evaluation. Where the data source in this study took data directly from the Indonesian Central Bureau of Statistics (BPS) in the form of softcopy entitled